AKSESIBILITAS INFORMASI GLOBAL DI KALANGAN MASYARAKAT PADA 2 DESA DI KECAMATAN BELOPA KABUPATEN LUWU (STUDI TENTANG PENGGUNAAN MEDIA ONLINE DI DAERAH PEDESAAN) - Muhammad Rayes Ibrahim; Hafied Cangara; Muhammad Yunus Amar (KAREBA : Jurnal Ilmu Komunikasi, 2020)
Digital divide in rural areas becomes important to be investigated so that later the results of this study can become literacy for the community in increasing the potential of human resources and social living standards through the use of information and communication technology. Research objectives (1) analyze the level of global information accessibility among rural communities in 4 community groups namely, groups of farmers, civil servants, students and housewives. This study uses a descriptive quantitative approach with a survey method to the study population originating from Belopa Village and Desa Senga Selatan. Samples taken amounted to 100 respondents with stratified sampling technique. Descriptive statistical analysis techniques are used to analyze the level of global information accessibility among rural communities. The results showed that (1) the level of global information accessibility among rural communities in the farmer group was quite low, where none of the 100 respondents surveyed used digital devices to access information through online media, (2) the level of global information accessibility in the group Civil servants are good enough where out of 100 respondents the most active PNS groups access information through online media, (3) the level of global information accessibility in the group of housewives is quite low where of the 100 respondents studied only 6% access information through online media.